2018
DOI: 10.1093/her/cyy038
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing patient uptake of an exercise referral scheme: a qualitative study

Abstract: Exercise referral schemes aim to increase physical activity amongst inactive individuals with or at risk of long-term health conditions. Yet many patients referred to these schemes (by health professionals) fail to take up the exercise opportunities on offer. Understanding factors influencing uptake to exercise referral schemes may help improve future attendance. Using the Socio-Ecological Model as a framework, this qualitative study aimed to explore factors influencing uptake to an exercise referral scheme ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 50 publications
5
19
0
Order By: Relevance
“…34 This is more likely to occur when enablers of exercise are present at multiple levels; including adequate resources and funding. 32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 This is more likely to occur when enablers of exercise are present at multiple levels; including adequate resources and funding. 32…”
Section: Discussionmentioning
confidence: 99%
“…27 A study of 43 sports physicians similarly found that while these physicians had positive attitudes to exercise counselling, only 51% indicated they often discussed physical activity with patients. 31 Studies of exercise attitudes and adherence to exercise training have focused largely on patient perspectives 32,33 ; few have considered treating clinician or implementers' perspectives, although these may influence patient behaviour, and offer valuable insights into improving patient adherence. 34 To our knowledge, there are no published studies assessing physicians' attitudes towards exercise or rehabilitation and their perspectives on perceived barriers and enablers of exercise for patients with PH.…”
Section: Introductionmentioning
confidence: 99%
“…One review suggests reason for referral as a predictor of scheme uptake [23], with those referred for a specific medical condition more likely to uptake, while other reviews report less clear findings [21]. A recent qualitative study [28] offers some insight into factors which influence uptake decisions, highlighting factors across the intrapersonal (past physical activity experience, motivation, competing demands), interpersonal (support and scheme understanding) and organisational (promotion, communication and cost) levels of the socioecological model. As portrayed above, the current evidence base appears somewhat conflicting, which is a likely reflection of the adoption of different uptake definitions and, even more so, the notable divergence in ERSs both within and across countries [29].…”
Section: Introductionmentioning
confidence: 99%
“…Although this study reviewed the effects of ERSs on change in physical activity, it does not consider the reasons for why participants chose to attend an ERS. Indeed, many factors influence uptake (Birtwistle et al 2018) and it seems likely would influence engagement throughout also. Some participants may have attended due to their own motivation to improve their health conditions, whereas, other participants may have only attended because their GP advised them to.…”
Section: Discussionmentioning
confidence: 99%